One-year post lockdown trajectories of mental health and impact of COVID-19 lockdown-related factors - Mongeau, Mathilde; Huo Yung Kai, Samantha; Bongard, Vanina; Coley, Nicola; Bérard, Emilie; Ferrières, Jean (Frontiers in Public Health, 2025)
IntroductionConcerns about the impact of restrictive measures on people’s wellbeing, especially mental health, were raised by the COVID-19 pandemic and related lockdown measures.MethodsIn this study, we examined longitudinal trajectories of mental health during the initial French lockdown period and up to one-year post-lockdown, among a representative sample of French adults aged over 50. We also assessed the impact of COVID-19 lockdown-related factors on mental health. A cohort of 534 individuals was enrolled during the first French lockdown in March 2020, and four telephone interviews were conducted during the lockdown, and at 1-, 6- and 12-months post-lockdown. Mental health was assessed using validated scores of anxiety and depression (GAD-7 and PHQ-9, respectively). Participants undergoing treatment for anxiety or depression at inclusion were excluded.ResultsOur analysis revealed a significant decrease in the proportion of individuals experiencing poor mental health (elevated GAD-7 or PHQ-9 > 4) from lockdown period to 1 month and 6 months post-lockdown. However, this improvement stopped at 12 months post-lockdown, likely reflecting the reinstatement of strict measures in 2021. We used logistic regression to identify factors independently associated with early and long-lasting deterioration in mental health (elevated GAD-7 or PHQ-9 > 4 at first or second interview that persisted over at least two interviews). History of anxiety, poor perceived global health, female gender, working during lockdown, not being in a relationship, and having a relative suspected of being COVID-positive were significantly associated with deterioration in mental health.DiscussionOur study highlights factors associated with a mental health impact during and following a lockdown in a representative sample of people, aged over 50 years old, thus at increased risk of severe COVID-19 and more likely to be subject to lockdown measures. These factors could be targeted in public health actions in future pandemics.